Acupuncture research in Taiwan - Wei-Liang Chen; Ching-Liang Hsieh (Elsevier, 2012)
Taiwan has a unique cultural milieu and integrated medical education so that is a bellwether for acupuncture research. Pioneer researches here on electrophysiology and neuroendocrine illustrate a crucial role of the central nervous system (CNS) plays in acupuncture treatment. With different frequency of stimulation, acupuncture can elicit different physiologic responses in the CNS and neuroendocrine systems. Researches in Taiwan on the autonomic nervous system (ANS), cardiovascular system, meridian theory, and acupoint specificity further shed light on the mechanism of acupuncture treatment. The strong research background in Taiwan enables clinicians here to conduct integrated trials on different disorders. Pain syndromes and neurologic disorders are the leading issues on acupuncture clinical trials. Novel concepts and studies hailed from Taiwan have great impact worldwide. In addition to pain syndromes, Taiwanese clinicians pay much attention to diverse kinds of diseases. This broadens the spectrum of acupuncture trials and clinical application of acupuncture treatment. The exploration conducted in Taiwan leads acupuncture research worldwide.